Microalgae in Waste Water Remediation - Kumar, Arun; Singh, Jay Shankar (CRC Press, 2021)
Microalgae in Waste Water Remediation aims to point out trends and current topics concerning the use of microalgae in wastewater treatment and to identify potential paths for future research regarding microalgaebased bioremediation. To achieve this goal, the book also assessing and analyzes the topics that attract attention among the scientific community and their evolution through time. This book will be useful to the students, scientists and policy makers concerned with the microalgae mediated management of wastewater effluents and its applications in overall future sustainable development.